Dissolved trace metal and nutrient samples from Arctic glacier runoff and iceberg fragments - Mark James Hopwood; Eric Pieter Achterberg (PANGAEA, 2025)
Freshwater samples from either runoff, or melted fragments of icebergs, were collected from sites around the Arctic. Iceberg fragments were melted at room temperature in the dark sealed inside LDPE bags. Samples were syringe filtered (0.20 μm) in the field and analyzed for dissolved trace metal (Mn, Fe, Co, Ni, Zn, Cd, and Pb) and macronutrient concentrations (nitrate, phosphate and dissolved silica). Trace metal samples were acidified to pH <2 with HCl after collection and then analyzed via ICP-MS at GEOMAR. Macronutrient samples were frozen after collection, returned to the home laboratory and analyzed using an autoanalyzer after defrosting overnight.